Impact of the COVID-19 Pandemic on the Detection of Leprosy in Micro-Regions with a High Risk of Illness in Minas Gerais, Brazil - Sarah Lamas Vidal; Daniele dos Santos Lages; Isabela Cristina Lana Maciel; Isabel Cristina Gonçalves Leite; Angélica da Conceição Oliveira Coelho; Francisco Carlos Félix Lana (Infectious Disease Reports)
Background: Leprosy control remains challenging in Brazil and has been aggravated by the COVID-19 pandemic. Objective: To analyze the impact of the COVID-19 pandemic on the epidemiological scenario of leprosy through the detection rate of new cases, the risk of illness, and the hidden prevalence of leprosy according to high-risk micro-region in Minas Gerais, Brazil. Methods: An ecological study conducted in the health micro-regions of Minas Gerais, using data on new leprosy cases diagnosed between 2015 and 2023. The annual detection rate of new cases, the risk of illness index and the hidden prevalence of leprosy were evaluated. The time trend was evaluated by calculating the annual percentage change (APC) of the detection rate, based on segmented linear regression, considered significant when it showed p < 0.05. Results: The state of Minas Gerais showed a significant negative annual increase between 2015 and 2020 (APC = −7.91; 95%CI −21.76–−1.72), and in 2020 it showed an inflection point, with an annual increase of 9.91 in the period from 2020 to 2023. When evaluating the hidden prevalence of leprosy in Minas Gerais, we observed a reduction in the estimates’ average from 2015–2019 (2.78) to 2020–2023 (2.00). The state as a whole showed an upward trend in the risk of illness, with the average index varying from 0.28 (medium risk) to 0.55 (high risk). Conclusions: The pandemic has had a considerable and heterogeneous impact on the detection of new cases, as well as on the risk of becoming ill and the hidden prevalence of leprosy, with repercussions for the control of the endemic in populations. There is a need to implement public health policies that prioritize the early identification of cases and ensure that vulnerable populations are monitored.